The Implementation of Elementary Student Character Values Among the Bajo Tribe through Pancasila Values as Character Building - Wajdi, Farid; Putra, Zulfikar (Universitas Sebelas Maret, 2021)
The purpose of this study was to determine the implementation of the character values of the Bajo tribe through the values of Pancasila as reinforcing character building in Bajo ethnic children, elementary school students. This type of qualitative research uses an ethnographic approach accompanied by data collection techniques through observation, interviews, and documentation. The data analysis technique in this study used the Spradley model. The findings of the research show that elementary school students on Masudu Island, most of whom have native Bajo ethnic backgrounds, have religious values, independence, discipline, social care, national spirit, mutual cooperation, and responsibility, as the implementation of Pancasila values and in accordance with character values. a nation that is seen in the daily lives of the children of the Bajo tribe who participate in studying at school, even though the school is located on one of the islands (in the sea).